Architecture of computing systems – ARCS 2016 : 29th International Conference, Nuremberg, Germany, April 4-7, 2016, Proceedings /: 29th International Conference, Nuremberg, Germany, April 4-7, 2016, Proceedings. (2016) - Unknown
No abstract available